Effects of co-exposure to lead and manganese on learning and memory deficits - Guan, Ruili; Wang, Tao; Dong, Xiaoru; Du, Kejun; Li, Juan; Zhao, Fang; Xu, Jie; Li, Bin; Zheng, Gang; Shen, Xuefeng; Cao, Baohua; Wang, Jing; et al. (Journal of environmental sciences (China), 2022)
Lead (Pb) and manganese (Mn) are common neurotoxins. However, individuals are subject to co-exposures in real life, and it is therefore important to study these metals in combination. Weaning Sprague-Dawley rats were given ad libitum access to drinking water solutions containing Pb (100 mg/L), Mn (2.5 mg/mL) or a mixture, and each treatment had its own minocycline (50 mg/(kg•day)) supplement group. The results showed a significant difference in spatial memory and induction levels of hippocampal long-term potentiation (LTP) in all exposure groups when compared with controls. The combined-exposure group exhibited the most pronounced effect when compared with each of the single-metal exposure groups. Microglia displayed activation at day 3 after exposure alone or in combination, while astrocytes showed activation at day 5, accompanied by decreased expression levels of GLAST, GLT-1, and GS. Furthermore, the levels of glutamate in the synaptic cleft increased significantly. When microglial activation was inhibited by minocycline, the activation of astrocytes and the expression of GLAST, GLT-1, and GS were both reversed. In addition, upon minocycline treatment, hippocampal LTP impairment and cognitive injury were significantly alleviated in each of the exposure groups. These results suggest that combined exposure to Pb and Mn can cause greater effects on cognition and synaptic plasticity when compared to single-metal exposure groups. The reason may involve abnormal activation of microglia leading to excessive regulation of astrocytes, resulting in glutamate reuptake dysfunction in astrocytes and leading to perturbed cognition and synaptic plasticity. [Display omitted]